FATORES DETERMINANTES DA PRÁTICA DE MÉTODOS CONTRACEPTIVOS ENTRE UNIVERSITÁRIAS DA ÁREA DA SAÚDE - Faray, Helone Eloísa Frazão Guimarães (2008)
The research objective the study of the determinants factors of the practical of contraceptive methods between colleges student of the health area. It was used of form with structuralized questions applied the 440 colleges student with age of 18 the 24 years of Faculdade Santa Terezinha (CEST). The analysis statistics it s being through the program Epi-Info and by means of the test qui-square. Amongst the searched colleges student 66.7% they had answered already to have initiated the sexual life. Most part of the colleges student initiated the sexual life with the age of 19 - 20 years 41.9%. In the first sexual relation 65.2% it used some contraceptive method. The used method more in the first sexual relation was condom 80.3%, currently 82.7% of the colleges student they use contraceptive and the preference continues being condom 84.9%. The majority of the colleges student declared to present frequency in the sexual relations of one or more times in week 54.2% and with a partner in the year 78.9%. The results in this population show that it has a proeminence for the bachelor condition, say to know condom as contraceptive method and affirm not to present doubts about the methods. Already they had initiated the sexual life and they had used contraceptive in the first relation presenting the frequency of one or more times in week and a partner in the last year.